Physical activity and sedentary behavior legislation in Canadian childcare facilities: an update - Leigh M. Vanderloo; Patricia Tucker (BMC, 2018)
Abstract Background Within the childcare sector, physical activity and sedentary behaviors are not legislated at a national level in Canada. Efforts have been undertaken to identify factors within childcare facilities which support and deter physical activity and sedentary behaviors. The purpose of this paper was to provide an amended review of the legislative landscape, at the provincial and territorial level, regarding physical activity and sedentary behaviors (via screen-viewing) in Canadian childcare centers. Methods Individual childcare acts and regulations for each province and territory were collected; documents were reviewed with a focus on sections devoted to child health, physical activity, screen time, play, and outdoor time. An extraction table was used to facilitate systematic data retrieval and comparisons across provinces and territories. Results Of the 13 provinces and territories, 8 (62%) have updated their childcare regulations in the past 5 years. All provinces provide general recommendations to afford gross motor movement; but the majority give no specific requirements for how much or at what intensity. Only 3 provinces (Northwest Territories, Nunavut, and Nova Scotia) explicitly mentioned daily physical activity while all provinces' and territories' required daily outdoor play. Only 1 province (New Brunswick) made mention of screen-viewing. Conclusions The variability in childcare regulations results in different physical activity requirements across the country. By providing high-level targets for physical activity recommendations, by way of provincial/territorial legislation, staff would have a baseline from which to begin supporting more active behaviors among the children in their care. Future research is needed to support translating physical activity policies into improved activity levels among young children in childcare and the role of screen-viewing in these venues.